Ефективність використання інструменту на термоформованому каркасі при фінішній обробці природних та штучних неметалевих матеріалів - Філатов, Ю.Д.; Крамар, В.Г.; Сідорко, В.І.; Замотаєв, П.В.; Філіпович, А.Ю.; Ковальов, С.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Experienced technology of the fabrication termocarcass to production polishing working element of the tool is described. The results of the estimation to capacity of the processing and quality
of the processed surfaces product from natural and synthetic non-metallic materials are presented.